Finite element analysis of immature teeth filled with MTA, Biodentine and Bioaggregate. (July 2020) - Eram, Afiya; Zuber, Mohammad; Keni, Laxmikant G; Kalburgi, Sagar; Naik, Rajaram; Bhandary, Shruti; Amin, Swathi; Badruddin, Irfan Anjum
Highlights: This article aims to analyse the fracture resistance of immature teeth reinforced with Mineral trioxide aggregate (MTA), Biodentine and Bioaggregate. 7 different models are analysed using finite element method. The results revealed that the 4 mm apical plug using MTA showed higher fracture resistance than 8.5 mm backfill. Abstract: Background and objective: Finite element based simulation has emerged as a powerful tool to analyse the tooth strength and its fracture characteristics. The aim of this study is to compare and evaluate the fracture resistance of immature teeth reinforcement with MTA, Biodentine and Bioaggregate as an apical plug and backfill material using Finite Element Method. Methods: A 3D finite element analysis model was generated using a simulated immature maxillary central incisor. Seven different models were developed representing (Model 1): control group having an immature tooth model without any reinforcement material; (Model 2): Mineral trioxide aggregate (MTA) as apical plug 4 mm; (Model 3): Biodentine as apical plug 4 mm; (Model 4): Bioaggregate as apical plug 4 mm; (Model 5): MTA filled in the entire root canal 8.5 mm; (Model 6): Biodentine filled in the entire root canal 8.5 mm; (Model 7): Bioaggregate filled in the entire root canal 8.5 mm. A force of 100 N was applied at an angle of 130° to the palatal surface of the tooth. Stress distribution at cemento‑enamel junction was measured using the Von Mises stress criteria. Results: It was found that the 4 mm apical plug using MTA showed higher fracture resistance when compared to 8.5 mm backfill using MTA. When MTA was replaced as backfill material by Biodentine and Bioaggregate, the von mises stress increased by 64% and 94% respectively. Conclusions: It is not desirable to restore the entire root canal of an immature teeth using same material due to higher stress concentration at the cervical region. Considering the shorter setting time and improved handling characteristics, Biodentine can be preferred over the time‑tested MTA as an apical plug.